Facile synthesis of truncated octahedron LiNi0.10Mn1.90O4 for high-performance Li-ion batteries. Issue 10 (July 2020) - Zhu, Jinyu; Liu, Qing; Xiang, Mingwu; Guo, Junming; Bai, Hongli; Liu, Xiaofang; Su, Changwei; Bai, Wei
Abstract: A truncated octahedron LiNi0.10 Mn1.90 O4 cathode material with (111), (100) and (110) crystal plane was easily synthesized by a solid-state combustion approach under heat treatment at 500 °C for 1 h and then 700 °C for 6 h. The as-prepared LiNi0.10 Mn1.90 O4 presents a particle distribution of approximately 200 nm and well maintains the characteristic spinel structure with no any impurities. Benefiting from the truncated octahedron morphology and Ni doping, lithium ions diffusion capability is enhanced and rebarbative Jahn-Teller distortion is also inhibited. Consequently, the LiNi0.10 Mn1.90 O4 cathode retains a superior capacity retention of 75.1% after 1000 cycles at 5 C, the corresponding LiMn2 O4 is only 44.08%. Even at a high current rate of 10 C, the LiNi0.10 Mn1.90 O4 delivers an initial capacity of 87.1 mAh/g and can undergo ultralong 2500 cycles.